Preparation method of nano-sol combined explosion-proof castable for hot-air furnace pipeline hot maintenance
By using nanosol combined with explosion-proof castable in hot air furnace pipelines, the problems of long construction cycles, poor economic benefits and easy explosion of materials in the prior art are solved, and the high strength and good thermal vibration stability of castable at high temperatures are achieved, which extends the service life and improves safety.
Patent Information
- Application Number
- CN202411471120.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-10-22
AI Technical Summary
The prior art has a long construction cycle and poor economic benefits in hot air furnace pipelines. Traditional materials are prone to burst at high temperatures, resulting in safety hazards and short service life.
Using nanosol combined with explosion-proof castable, a castable with good fluidity and easy construction is prepared by adding mullite, brown corundum, composite ultrafine powder, cyanite, boron carbide powder, metal aluminum powder, polypropylene explosion-proof fiber, nanosilicon sol and high-efficiency water reducer. The castable is slightly expanded in volume at high temperature and does not produce microcracks. It solidifies 1-2 hours after vibration and molding, and can be put into use without maintenance and baking.
The castable material has high strength and good thermal vibration stability at high temperatures, can withstand the erosion and erosion of high-speed hot air, and its service life can reach more than 5 years, significantly shortening the construction cycle, improving economic benefits, and reducing safety hazards.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ironmaking, and in particular relates to a method for preparing a nano-sol combined explosion-proof castable used for hot-state maintenance of hot blast furnace pipelines. Background Art
[0002] The hot blast furnace pipe is a device that transports the high-temperature air generated by the hot blast furnace to the blast furnace. The air temperature generated by the hot blast furnace supporting modern large blast furnaces can reach up to 1250~1300℃. The refractory lining of the hot blast duct is generally divided into three layers, from the inside to the outside, they are the working layer, the insulation layer, and the spray layer. The working layer and the insulation layer are both built with refractory bricks. The spray layer generally uses refractory spray paint, which plays the role of leveling and protecting the steel structure shell. In blast furnace production, when the high-temperature hot air flows at high speed in the pipeline, it will cause erosion to the refractory lining in the pipeline. Under the action of long-term thermal stress, micro-cracks will appear in the refractory lining. In severe cases, the refractory bricks will even fall off and collapse, and there is a risk of burning through the pipeline shell. Therefore, for production safety, if local heating and redness are found on the outer surface of the hot blast duct during daily operation, it is necessary to carry out maintenance immediately to eliminate safety hazards.
[0003] According to the different degrees of damage to the lining material, if only local refractory bricks have cracks, the refractory bricks of the working layer have not fallen off, and the hot air only reaches the spray layer through the cracks, then pressure grouting can be carried out by opening holes in the reddened parts without stopping the wind. The refractory grouting material fills the tiny cracks of the lining material under pressure, which can temporarily solve the reddening of the outer surface of the pipeline. If the refractory bricks of the working layer fall off or even collapse on a large scale, pressure grouting cannot solve the problem. Usually, after the wind is stopped, when the temperature in the pipeline drops below the safety line, people enter the pipeline manually to clean up the loose and fallen refractory bricks, and rebuild them. Cement combined with corundum mullite castables are also used in some parts. This material has high strength and good high-temperature performance, but the disadvantage is that it needs long-term maintenance and slow heating to the working temperature after pouring. The working temperature is too high. When heated too quickly, the water in the castable quickly vaporizes and generates a large amount of water vapor in a short time. The water vapor accumulates inside the castable to form a very high water vapor pressure. If the water vapor pressure exceeds the strength limit of the castable, it will cause the castable to burst, resulting in serious production safety accidents. Therefore, cement-bonded castables generally need to be cured for at least 48 hours, and they need to be baked for another 5-7 days after demolding. The water in the castable is slowly discharged during the slow heating process. The construction period is very long. In addition, after the polypropylene explosion-proof fibers used in the castable in the prior art are melted, they are distributed in the construction body to form a network of pores, which can open the water vapor channel, reduce internal stress and prevent bursting. However, the pores formed are easily eroded, which is one of the main reasons for the reduced service life.
[0004] In short, if traditional materials and construction techniques are used, whether it is reconstruction or pouring construction using cement-bonded castables, the construction period will be very long, the economic benefits will be poor, and the normal production of the blast furnace will be seriously interfered with. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a method for preparing a nano-sol combined explosion-proof castable for hot-air furnace pipeline hot maintenance. The castable has good fluidity, simple construction, and a high degree of mechanization. After being vibrated and formed for 1-2 hours and solidified, it can be put into use without maintenance and baking. The volume of the castable expands slightly at high temperature and no microcracks are generated. It has high medium and high temperature strength, excellent thermal vibration stability, and is resistant to scouring and erosion by high-temperature and high-speed hot air. The service life is expected to be more than 5 years.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is:
[0007] A nano-sol combined explosion-proof castable for hot-air furnace pipeline hot maintenance, the original materials are: mullite, brown corundum, composite ultrafine powder, kyanite, boron carbide powder, metal aluminum powder, polypropylene explosion-proof fiber, nano-silica sol and high-efficiency water reducing agent.
[0008] The weight proportions of the raw materials added in the present invention are: 25-50 parts of mullite, 20-40 parts of brown corundum, 10-25 parts of composite ultrafine powder, 5-10 parts of kyanite, 5-15 parts of boron carbide powder, 0.1-5 parts of metal aluminum powder, 0.1-5 parts of polypropylene explosion-proof fiber, 5-15% of the total weight of the raw materials added in nano-silica sol, and 0.1-15% of the total weight of the raw materials added in high-efficiency water reducing agent.
[0009] The particle size of the mullite is 0-8 mm;
[0010] The particle size of the brown corundum is 0-3 mm;
[0011] The particle size of the boron carbide powder is 0-0.088 mm;
[0012] Therefore, the particle size of kyanite is 0-0.5mm;
[0013] The particle size of the metal aluminum powder is 0-0.088 mm;
[0014] The high-efficiency water reducer is a polycarboxylate water reducer;
[0015] The composite ultrafine powder is a composite of activated alumina micropowder and silicon dioxide micropowder.
[0016] The preparation method of the nano-sol combined explosion-proof castable for hot-air furnace pipeline hot maintenance is as follows:
[0017] Step 1: Processing of polypropylene explosion-proof fiber:
[0018] First, 3-10mm polypropylene explosion-proof fiber is uniformly mixed with nano-silica sol, and then composite ultrafine powder and boron carbide powder are added and stirred, so that the composite ultrafine powder and boron carbide powder are evenly wrapped around the polypropylene explosion-proof fiber. After drying and solidification, they are packaged separately for use; the total weight of nano-silica sol, composite ultrafine powder and boron carbide powder added is 20-40% of the total weight of the polypropylene explosion-proof fiber; the ratio of nano-silica sol, composite ultrafine powder and boron carbide powder added is 2:1:1;
[0019] Step 2: weigh 25-50 parts of mullite, 20-40 parts of brown corundum, 10-25 parts of composite ultrafine powder, 5-10 parts of kyanite, 5-15 parts of boron carbide powder, and 0.1-5 parts of metal aluminum powder, mix them evenly, and then bag them for later use;
[0020] Step 3: The nano-silica sol is packaged separately;
[0021] Step 4: At the construction site, use a forced mixer to mix the mixture obtained in step 2, 0.1-5 parts of the treated polypropylene explosion-proof fiber obtained in step 1, 5-15% of the total weight of the original material in step 2, and 0.1-1% of the high-efficiency water reducing agent in step 2 to obtain the nano-sol combined explosion-proof castable for hot repair of hot blast furnace pipelines; after vibrating and molding for 1-2 hours and curing, it can be put into use without maintenance and baking.
[0022] Under the high temperature environment of use, the polypropylene explosion-proof fiber begins to soften, shrink, melt, and finally form pores. The active alumina powder and silica powder in the composite ultrafine powder wrapped by the polypropylene explosion-proof fiber react at high temperature to form mullite; the boron carbide powder can form B2O3 at high temperature; a composite phase of a network crystal structure of 3Al2O3·2SiO2-B2O3 interwoven is formed in situ on the surface of the pores, and the whiskers of the composite phase are interwoven with each other, which not only enhances the high temperature resistance of the pore surface, but also has an antioxidant effect, thereby solving the technical problem that the pores formed after the polypropylene explosion-proof fiber is melted are easily eroded in the prior art.
[0023] When the nano silica sol prepared by the present invention is combined with the explosion-proof castable and used in the hot blast furnace pipeline, during the heating process, the water in the nano silica sol gradually evaporates, and the condensation reaction between the silanol groups continues to proceed, so that the network structure is more compact and stable, the sol reacts with the components in the refractory matrix at high temperature to generate mullite, and the boron carbide powder can form B2O3 at high temperature, thereby partially forming a high-melting-point composite phase 3Al2O3·2SiO2-B2O3, these high-melting-point composite phases not only enhance the high-temperature resistance of the material, but also promote the direct combination between the sol and the refractory aggregate, and further improve the overall strength of the material; the microstructure of the composite ultrafine powder is spherical, and the particle size reaches the nanometer level, which not only adheres to the surface of the composite phase structure to form a firm skeleton effect, but also significantly improves the strength of the final product; some nano powder particles penetrate into the gaps of the high-melting-point composite phase 3Al2O3·2SiO2-B2O3, playing a secondary protection role, thereby improving sufficient anti-penetration and erosion resistance.
[0024] In addition, composite ultrafine powder technology is used. Under high temperature conditions, nano-SiO2 in silica sol can react with active alumina in the matrix to produce 3Al2O3·2SiO2 high-temperature stable phase. Mullite has excellent high temperature resistance, thermal shock resistance and erosion resistance, which plays a key role in improving the high temperature performance of castables.
[0025] The microstructure of the activated alumina powder and silica powder in the composite ultrafine powder are spherical, and the particle size reaches nanometer level, so the reaction activity is very high. At room temperature, they can fill the gaps between materials, reduce the amount of liquid added, and improve the density of the material. At high temperature, they can react to form mullite, produce a certain amount of expansion, improve the high temperature strength and thermal vibration stability of the material, increase the density of the material, and avoid cracks.
[0026] Kyanite can decompose to produce mullite at high temperature and is accompanied by volume expansion. The addition of kyanite is mainly to compensate for shrinkage and increase volume stability.
[0027] Boron carbide powder reacts at high temperature to form columnar crystals. These crystals are distributed in the matrix and gaps of the castable, which can effectively reduce the porosity and improve the density and strength of the castable. Boron carbide powder can also significantly improve the medium-temperature strength of the castable. Boron carbide powder can form a dense B2O3 oxide film at high temperature. This film can effectively isolate oxygen from the contact with the inside of the castable and has an antioxidant effect, which is of great significance for improving the service life and stability of the castable.
[0028] High-efficiency water reducer can reduce the amount of liquid added to the castable, improve fluidity, and thus increase the material density and room-temperature strength.
[0029] The present invention uses brown corundum and mullite with high corrosion resistance and scour resistance, which greatly improves the corrosion resistance of the castable and improves the service life of the hot blast furnace pipeline lining; the present invention can be put into use without maintenance and baking after vibrating and molding for 1-2 hours in step 4 and curing, because the present invention uses nano silica sol, which has higher reaction activity than ordinary silica sol, and the nano-scale sol particles are evenly dispersed in the system. This evenly dispersed structure enables heat to be transferred relatively evenly during rapid heating, and local thermal stress concentration will not occur; compared with cement-bonded castables, cement particles are larger and unevenly distributed, which easily leads to local moisture concentration and thermal stress concentration, while the nano-size of the sol particles enables it to be better filled between the refractory aggregates to form a more even The sol will gradually transform into a gel during the drying and heating process, forming a strong and flexible bonding structure. This bonding structure can provide sufficient strength to maintain the integrity of the castable, and has a certain flexibility to buffer the thermal expansion and contraction during the heating process. During the heating process of the sol-bonded castable, the water is discharged relatively slowly and evenly. This is because the gel structure formed by the sol has a certain binding effect on the water, so that the water will not evaporate and escape rapidly in a short time. The slow and uniform water discharge can avoid the instantaneous high pressure caused by the rapid vaporization of water, thereby reducing the risk of bursting. At the same time, this slow water discharge process also helps the castable to gradually form a stable structure during the heating process and improve its thermal shock resistance. This overcomes the technical difficulties that other binder-bonded castables generally need to be cured for at least 48 hours, and need to be baked for another 5-7 days after demolding, and the water in the castable is slowly discharged during the slow heating process, and the construction period is very long.
[0030] The nano-sol combined explosion-proof castable for hot-air furnace pipeline hot maintenance prepared by the present invention has good fluidity, simple and fast construction, high mechanization degree, and can be put into use after being vibrated and molded for 1-2 hours and solidified without additional maintenance or baking, thus saving time and cost and having remarkable economic benefits. DETAILED DESCRIPTION
[0031] The following examples illustrate the implementation and features of the present invention, but the present invention is not limited to the following embodiments.
[0032] Embodiment 1:
[0033] The preparation method of the nano-sol combined explosion-proof castable for hot-air furnace pipeline hot maintenance is as follows:
[0034] Step 1. Treatment of polypropylene explosion-proof fiber: first mix 3mm polypropylene explosion-proof fiber with nano-silica sol evenly, then add composite ultrafine powder and boron carbide powder and stir, so that the composite ultrafine powder and boron carbide powder are evenly wrapped around the polypropylene explosion-proof fiber, and after drying and solidification, they are packaged separately for standby use; the total weight of nano-silica sol, composite ultrafine powder and boron carbide powder added is 20% of the total weight of polypropylene explosion-proof fiber; the ratio of nano-silica sol, composite ultrafine powder and boron carbide powder added is 2:1:1;
[0035] Step 2: weigh 25 parts of mullite, 20 parts of brown corundum, 10 parts of composite ultrafine powder, 5 parts of kyanite, 5 parts of boron carbide powder, and 0.1 parts of metal aluminum powder, mix them evenly, and then bag them for later use;
[0036] Step 3: The nano-silica sol is packaged separately;
[0037] Step 4: At the construction site, use a forced mixer to mix the mixture obtained in step 2, 0.1 parts of the treated polypropylene explosion-proof fiber obtained in step 1, 5% of the total weight of the original material in step 2, and 0.1% of the total weight of the polycarboxylic acid water reducer in step 2, to obtain the nano-sol combined explosion-proof castable for hot blast furnace pipeline hot maintenance; after vibrating and molding for 1 hour and curing, it can be put into use without curing and baking.
[0038] Embodiment 2:
[0039] The preparation method of the nano-sol combined explosion-proof castable for hot-air furnace pipeline hot maintenance is as follows:
[0040] Step 1. Treatment of polypropylene explosion-proof fiber: first mix 6mm polypropylene explosion-proof fiber with nano-silica sol evenly, then add composite ultrafine powder and boron carbide powder and stir, so that the composite ultrafine powder and boron carbide powder are evenly wrapped around the polypropylene explosion-proof fiber, and after drying and solidification, they are packaged separately for standby use; the total weight of nano-silica sol, composite ultrafine powder and boron carbide powder added is 30% of the total weight of polypropylene explosion-proof fiber; the ratio of nano-silica sol, composite ultrafine powder and boron carbide powder added is 2:1:1;
[0041] Step 2: weigh 40 parts of mullite, 30 parts of brown corundum, 15 parts of composite ultrafine powder, 7 parts of kyanite, 10 parts of boron carbide powder, and 3 parts of metal aluminum powder, mix them evenly, and then bag them for later use;
[0042] Step 3: The nano-silica sol is packaged separately;
[0043] Step 4: At the construction site, use a forced mixer to mix the mixture obtained in step 2, 3 parts of the treated polypropylene explosion-proof fiber obtained in step 1, 10% of the total weight of the original material in step 2, and 0.5% of the total weight of the polycarboxylic acid water reducer in step 2, to obtain the nano-sol combined explosion-proof castable for hot repair of hot blast furnace pipelines; after vibrating and molding for 1.5 hours and curing, it can be put into use without maintenance and baking.
[0044] Embodiment 3:
[0045] The preparation method of the nano-sol combined explosion-proof castable for hot-air furnace pipeline hot maintenance is as follows:
[0046] Step 1. Treatment of polypropylene explosion-proof fiber: First, evenly mix 9mm polypropylene explosion-proof fiber with nano-silica sol, then add composite ultrafine powder and boron carbide powder and stir, so that the composite ultrafine powder and boron carbide powder are evenly wrapped around the polypropylene explosion-proof fiber, and after drying and solidification, they are packaged separately for standby use; the total weight of nano-silica sol, composite ultrafine powder and boron carbide powder added is 40% of the total weight of polypropylene explosion-proof fiber; the ratio of nano-silica sol, composite ultrafine powder and boron carbide powder added is 2:1:1;
[0047] Step 2: weigh 50 parts of mullite, 40 parts of brown corundum, 25 parts of composite ultrafine powder, 10 parts of kyanite, 15 parts of boron carbide powder, and 5 parts of metal aluminum powder, mix them evenly, and then bag them for later use;
[0048] Step 3: The nano-silica sol is packaged separately;
[0049] Step 4: At the construction site, use a forced mixer to mix the mixture obtained in step 2, 5 parts of the treated polypropylene explosion-proof fiber obtained in step 1, 15% of the total weight of the original material in step 2, and 1% of the total weight of the polycarboxylic acid water reducer in step 2, to obtain the nano-sol combined explosion-proof castable for hot repair of hot blast furnace pipelines; after vibrating and molding for 1-2 hours and curing, it can be put into use without maintenance and baking.
[0050]
[0051] The above three embodiments have a scientific and reasonable combination of raw materials, and the fluidity of the castables produced is very good. The performance indicators measured by sample preparation are higher than those of the prior art. In particular, the medium-temperature strength is greatly improved due to the addition of boron carbide powder compared to traditional cement-bonded castables. The line change rate after firing is slightly expanded, so that the lining material has good high-temperature volume stability, and will not have air leakage due to volume shrinkage, further enhancing the erosion and abrasion resistance and thermal vibration stability, extending the service life of the lining material, and is beneficial to the iron plant's goal of reducing costs and increasing efficiency.
Claims
1. A method for preparing a nano-sol combined explosion-proof castable for hot-air furnace pipeline hot maintenance, Features: Step 1: Treatment of polypropylene explosion-proof fiber: firstly mix 3-10mm polypropylene explosion-proof fiber with nano-silica sol, then add composite ultrafine powder and boron carbide powder and stir, so that the composite ultrafine powder and boron carbide are evenly wrapped around the explosion-proof fiber, and after drying and solidification, they are packaged separately for standby use; the composite ultrafine powder is a composite of activated alumina micropowder and silica micropowder; the microstructures of activated alumina micropowder and silica micropowder in the composite ultrafine powder are both spherical, and the particle size reaches nanometer level; Step 2: weigh 25-50 parts of mullite, 20-40 parts of brown corundum, 10-25 parts of composite ultrafine powder, 5-10 parts of kyanite, 5-15 parts of boron carbide, and 0.1-5 parts of metal aluminum powder, mix them evenly, and then bag them for later use; Step 3: The nano-silica sol is packaged separately; Step 4: At the construction site, a forced mixer is used to mix the mixture obtained in step 2, 0.1-5 parts of the treated explosion-proof fiber obtained in step 1, 5-15% of the total weight of the original material in step 2, and 0.1-1% of the high-efficiency water reducing agent in step 2 to obtain a nano-sol combined explosion-proof castable for hot repair of hot blast furnace pipelines; after vibrating and molding for 1-2 hours and curing, it can be put into use without maintenance or baking.
2. The method for preparing a nano-sol combined explosion-proof castable for hot-air stove pipeline hot maintenance according to claim 1, characterized in that: The total weight of the nano-silica sol, composite ultrafine powder and boron carbide powder added in step one is 20-40% of the total weight of the explosion-proof fiber; the ratio of the nano-silica sol, composite ultrafine powder and boron carbide powder added is 2:1:
1.
3. The method for preparing a nano-sol combined explosion-proof castable for hot-air stove pipeline hot maintenance according to claim 1, characterized in that: The particle size of the boron carbide powder in step 1 and step 2 is 0-0.088 mm.
4. The method for preparing a nano-sol combined explosion-proof castable for hot-air stove pipeline hot maintenance according to claim 1, characterized in that: The particle size of kyanite is 0-0.5mm.
5. The method for preparing a nano-sol combined explosion-proof castable for hot-air stove pipeline hot maintenance according to claim 1, characterized in that: The particle size of the metal aluminum powder is 0-0.088mm.
6. The method for preparing a nano-sol combined explosion-proof castable for hot-air stove pipeline hot maintenance according to claim 1, characterized in that: The high-efficiency water reducer is polycarboxylate water reducer.
Citation Information
Patent Citations
Manufacturing method of quick-drying explosion-proof castables by recovery and utilization of scrap iron trough reclaimed materials
CN103936441A